The Effect of Competence and Work Environment on Motivation and its Effects on Employee Performance - Muhammad Fathir Poetra Halilintar; Muhamad Halilintar (PT. ALHAFI BERKAH INDONESIA, 2025)
The purpose of this study is to deduce the extent of how Competence and the Work Environment influences Employee Motivation as well as their role on affecting Employee Performance at PT. Klinik Mega Kartika in Depok, West Java. The primary data used in this research was collected from respondents' answers based on a questionnaire distributed to 39 individuals. The data processing method for this study uses path analysis with SPSS version 20.0. Statistical testing includes the individual parameter significance test (t-test), simultaneous significance test (F-test), and the Sobel test. The results of this study indicate that, simultaneously, the variables of Competence, Work Environment, and Motivation have a significant effect on employee performance. Partially, the analysis shows the following: Firstly, Competence has an effect on Employee Performance, Secondly Work Environment has an effect on Employee Performance, and Third, Motivation has a significant effect on Employee Performance.